Analisis Penyebab Rendahnya Literasi Siswa di Sekolah Dasar - Muthia; Salsabila Pratiwi (Jurnal Riset Guru Indonesia, 2024)
This article examines the factors contributing to the low literacy levels at SD Negeri 4 Barru, particularly in grade V. The skills of listening, speaking, reading, and writing are crucial elements in 21st-century education. Although the government has launched the School Literacy Movement (GLS) program to enhance literacy skills, many students still face challenges. This research employs a qualitative descriptive method, gathering data through observation and interviews. The analysis indicates that the causes of low literacy among students can be categorized into two groups: student factors and school factors. Student factors include low reading interest, inadequate foundational skills, family socio-economic conditions, and the impact of gadget and television use. On the other hand, school factors encompass limitations in facilities and reading materials, as well as ineffective teaching methods. The findings of this study are expected to serve as a reference for formulating solutions to improve literacy at the elementary school level.